The case of slobodan milosevic at the international criminal tribunal for the former yugoslavia and its perceptions in serbia and in the world - Utku, Hatice Ahsen (My University, 2012)
yetçilik, Liderlik, Sırbistan, Milošević ÖZET ESKİ YUGOSLAVYA SAVAŞ SUÇLULARI MAHKEMESİ’NDE MİLOŠEVİĆ DAVASI VE SIRBİSTAN’DA VE DÜNYADAKİ ALGILARI Balkanlar farklı etnik ve dini topluluklar arasında tarih boyunca çatışma ve bir arada yaşama tecrübelerine tanıklık etmiştir. Farklılıklar tarih boyunca süregelirken, liderlik, milliyetçilik ve etnik çatışma ile birlikte gündeme gelmektedir. Bu bakımdan, Slobodan Milošević’in liderliği, milliyetçi duyguların ve etnik çatışmaların tahrik edilmesiyle liderlik miti yaratılması bağlamında incelenmiştir. Bu açıdan, Eski Yugoslavya Savaş Suçluları Mahkemesi de Milošević’in liderlik miti yaratma çabalarına sahne olmuştur. Tez, 1990’larda Balkanlar’da patlak veren savaş ile Milošević davasını, Milošević’in milliyetçi bir söylem kullanarak bir liderlik miti yaratması bağlamında analiz etmiştir. Nationalism, Leadership, Serbia, Milošević

THE CASE OF SLOBODAN MILOSEVIC AT THE INTERNATIONAL CRIMINAL TRIBUNAL FOR THE FORMER YUGOSLAVIA AND ITS PERCEPTIONS IN SERBIA AND IN THE WORLD The Balkans region has witnessed processes of conflicts and coexistence among different ethnic and religious communities throughout history. While differences have always existed in the history, the notion of leadership come to the agenda in relation to nationalism and ethnic conflict. In this respect, the leadership of Slobodan Milošević is observed in terms of creating the myth of leadership by the incitement nationalist sentiments and ethnic conflicts. In this sense, the International Criminal Tribunal for the Former Yugoslavia also has been stage for Milošević’s effort of creating the myth of leadership. The thesis analyzes the process of war in the Balkans in the 1990s and the Milošević trial in terms of the creation of a myth of a leader of by Milošević by using a nationalist discourse.
Keywords: Liderlik; Milliyetçilik; Sırbistan